Induction of NO synthesis in roots of wheat plantlets and development of their heat resistance by exogenous L-arginine and nitrate - Karpets, Yu.V.; Kolupaev, Yu.E.; Dmitriev, A.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
The treatment of roots of intact plantlets of wheat (Triticum aestivum L.) with L-arginine and sodium nitrate caused an increase of the content of nitric oxide (NO) in them and raised the resistance to the damaging heating. The arginine-dependent increase of the NO content was suppressed by the pretreatment of roots with NO-synthase inhibitor L-NAME (NG-nitro-L-arginine methyl ester), and the nitrate-dependent one — with nitrate reductase inhibitor, sodium tungstate. These inhibitors eliminated also the positive influence of exogenous L-arginine and nitrate on the heat resistance of plantlets that confirms the crosstalk of such influence with the process of nitric oxide synthesis. At the combined treatment of plantlets with L-arginine and nitrate, their influence on the content of nitric oxide in roots and the development of the heat resistance of plantlets was leveled. The oppression of the nitrate-dependent formation of nitric oxide in plantlets roots, caused by L-arginine, was partially removed by NO-synthase inhibitor L-NAME. Thus, the data on the antagonism of the arginine- and nitrate-dependent pathways of nitric oxide synthesis in plant cells are obtained for the first time.